Mapping and Harmonizing Qanun on Sharia Financial Institutions - Faisal Faisal; Jumadiah Jumadiah; Layla Tunnur; Diras Diras; Nanda Amalia (Faculty of Law, Sriwijaya University, Indonesia, 2024)
Law No. 11/2006 on the Government of Aceh (Aceh Government Law) has mandated Aceh Qanun No. 11/2018 on ShariaFinancial Institutions. A thorough and integrated regulatory infrastructure must support the Qanun on Sharia Financial Institutions. The Qanun on Sharia Financial Institutions regulates that all Sharia Financial Institutions operating in Aceh must transition from the conventional to the Sharia system. However, in reality, many norms still need to be synchronised with national rules so that Sharia Financial Institutions do not run optimally. This study aims to map and harmonise legal issues and purification of Qanun on Sharia Financial Institutions in the future. The method used is normative juridical with a qualitative approach and uses secondary data. The study found that first, the mapping of Qanun on Sharia Financial Institutions still has articles that overlap and need to be more technical with the inclusion of the year that has passed. In addition, an article includes administrative sanctions that are not implemented. Then, there are ambiguous norms that cause multiple interpretations. Second, Qanun on Sharia Financial Institutions needs harmonisation with higher laws and regulations. In addition, several Governor and Regent Regulations and other technical rules are required to maximise the implementation. Third, purification is needed by revising articles that overlap with the rules above and harmonising them with national regulations in Islamic finance.